The gene encoding the T-box factor Tbx2 is a target for the microphthalmia-associated transcription factor in melanocytes. - Carreira, S; Liu, B; Goding, C (2000)
Commitment to the melanocyte lineage is characterized by the onset of microphthalmia-associated transcription factor (Mitf) expression. Mitf plays a fundamental role in melanocyte development, with mice lacking Mitf being entirely devoid of pigment cells. In the absence of functional Mitf protein, melanoblasts expressing Mitf mRNA disappear around 2 days after their first appearance either by apoptosis or by losing their identity and adopting an alternative cell fate. The role of Mitf must therefore be to regulate genes required for melanoblast survival, proliferation, or the maintenance of melanoblast identity. Yet to date, Mitf has been shown to regulate genes such as Tyrosinase, Tyrp-1, and Dct, which are required for pigmentation, a differentiation-specific process. Because expression of these genes cannot account for the complete absence of pigment cells in Mitf-negative mice, Mitf must regulate the expression of other as yet uncharacterized genes. Here we provide several lines of evidence to suggest that Mitf may regulate the expression of the Tbx2 transcription factor, a member of the T-box family of proteins implicated in the maintenance of cell identity. First, isolation and sequencing of the entire murine Tbx2 gene revealed that the Tbx2 promoter contains a full consensus Mitf recognition element; second, Mitf could bind the promoter in vitro and activate Tbx2 expression in vivo in an E box-dependent fashion; and third, Tbx2 is expressed in melanoma cell lines expressing Mitf, but not in a line in which Mitf expression was not detectable. Taken together, with the fact that Tbx2 is expressed in Mitf-positive melanoblasts and melanocytes, but not in Mitf-negative melanoblast precursor cells, the evidence suggests that the Tbx2 gene may represent one of the first known targets for Mitf that is not a gene involved directly in the manufacture of pigment.